A Practical Tool for Measuring Home‐Based Cardiac Rehabilitation Self‐Management Behavior: A Multiphase Cross‐Sectional Study - Zhen Yang; Na Hu; Fengpei Zhang; Yu Gao; Chunqi Zhang; Aiping Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Optimal self‐management is the key to home‐based cardiac rehabilitation for patients with heart disease. At present, there is a lack of a specific assessment tool to evaluate the home‐based cardiac rehabilitation self‐management behavior in patients with heart disease. Therefore, the aim of this study was to develop the Home‐Based Cardiac Rehabilitation Self‐Management Scale and validate its psychometric properties among patients with coronary heart disease. Methods and Results A multiphase cross‐sectional study was conducted that study covered 3 phases: (1) item generation and revision, (2) item evaluation and preliminary exploration, and (3) assessment of the psychometric properties of the scale. A scale with 21 items was developed to measure the home‐based cardiac rehabilitation self‐management behavior. The content validity index of the scale was 0.980. In exploratory factor analysis, the 5‐factor structure supported by eigenvalues and screen plot explained 74.326% of the total variation. In confirmatory factor analysis, all fitting indicators were acceptable, further supporting the construct validity of the scale. The criterion validity of the scale was 0.783. In the reliability analysis, the Cronbach's α coefficient of the scale was 0.882, with a dimensionality range of 0.780 to 0.936. The split‐half reliability coefficient and test–retest reliability coefficient were 0.774 and 0.770, respectively. Conclusions This study is the first to develop and validate a practical tool. This scale can comprehensively and accurately assess the self‐management behavior of patients with heart disease in a home‐based cardiac rehabilitation environment.